(untitled) - Lock, Margaret M. (Berkeley, 1980)
An excellent description and analysis of East Asian medicine ... Based on fieldwork conducted in Japan during 1973 and 1974, which involved the use of a variecy of participant-observer techniques, as well as extensive reading in primary and secondary sources in Japanese and English, Lock's study makes a significant contribution to our understanding of an important dimension of life in Japan. . . In well-written chapters dealing with the philosophical foundations and historical development of East Asian medicine, Japanese attitudes regarding health, illness, and the human body, detailed description of kanpo clinics, herbal pharmacies, acupuncture and moxibustion clinics, shiatsu and anma clinics, East Asian medical schools as well as the interactions between various providers and patients (customers), Lock develops the cultural thesis.
Keywords: Nhân học y học,Medicine, Chinese,Medical anthropology,Medical anthropology,Y học, Trung Quốc; Nhật Bản,Japan,Japan,Japan,Nhật Bản